Sistem Penunjang Keputusan Dalam Pemilihan Hewan Peliharaan Untuk Anak Dengan Metode AHP - Fithry Tahel; Frans Ikorasaki (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2021)
In connection with World Animal Day which falls on October 4, many studies have revealed that raising animals can actually provide many benefits for child development. Kids always love animals! Try taking your little one on a safari to the zoo and see their reaction. He will be happy, curious, and there is little fear. Well, what if your little one is invited to raise animals at home. Seeing that your little one is very happy when they meet cute animals such as dogs, cats, or rabbits out there, maybe this can be a consideration for parents to give them a pet. Not only can you be a friend to accompany your little one to play with, keeping a pet at home can also provide many other benefits for your little one. As a parent, it takes a lot of consideration to choose a pet that is suitable for children. Many things need to be considered, starting from the size of the animal, how to care for it, to determine whether the child has allergies to certain pets. Choosing a pet for children does need to be careful. However, the pet you choose can indirectly train empathy and a sense of responsibility in your child. In addition, the presence of pets allows children to have friends to play with and no longer feel bored. The presence of the right pet will have a good impact on your child. However, if you choose the wrong pet, it will have a negative impact on the child. It's not that pets make you happy and fun, it makes you more careful. With a decision support system using the AHP (Analytical Hierarchy Process) method, the AHP method is used in selecting pets for children.